Mefloquine enhances the efficacy of anti-PD-1 immunotherapy via IFN-γ-STAT1-IRF1-LPCAT3-induced ferroptosis in tumors - Jing Chen; Jie Wu; Xiang Chen; Qian Tao; Nian Liu; Cong Peng (Journal for ImmunoTherapy of Cancer)
Background Ferroptosis plays an important role in enhancing the efficacy of anti-programmed cell death 1 (PD-1) immunotherapy; however, the molecular mechanisms by which tumor ferroptosis sensitizes melanoma and lung cancer to anti-PD-1 immunotherapy have not been elucidated.Methods Cytotoxicity assays, colony formation assays, flow cytometry and animal experiments were used to evaluate the effects of mefloquine (Mef) on survival and ferroptosis in melanoma and lung cancer. RNA sequencing, Real-time quantitative PCR (qRT-PCR), western blotting, chromatin immunoprecipitation-qPCR and flow cytometry were used to determine the molecular mechanisms by which Mef regulates lysophosphatidylcholine acyltransferase 3 (LPCAT3). The relationship between LPCAT3 and the efficacy of anti-PD-1 immunotherapy was verified via a clinical database and single-cell RNA sequencing (ScRNA-Seq).Results In this study, we discovered that Mef induces ferroptosis. Furthermore, treatment with Mef in combination with T-cell-derived interferon-γ (IFN-γ) enhanced tumor ferroptosis and sensitized melanoma and lung cancer cells to anti-PD-1 immunotherapy. Mechanistically, Mef upregulated the expression of LPCAT3, a key gene involved in lipid peroxidation, by activating IFN-γ-induced STAT1-IRF1 signaling, and knocking down LPCAT3 impaired the induction of ferroptosis by Mef+IFN-γ. Clinically, analysis of the transcriptome and single-cell sequencing results in patients with melanoma showed that LPCAT3 expression was significantly lower in patients with melanoma than in control individuals, and LPCAT3 expression was positively correlated with the efficacy of anti-PD-1 immunotherapy.Conclusions In conclusion, our study demonstrated a novel mechanism by which LPCAT3 is regulated, and demonstrated that Mef is a highly promising new target that can be utilized to enhance the efficacy of anti-PD-1 immunotherapy.